Determination of suitable groundwater quality for agriculture by using GIS application in Bantul Regency, Yogyakarta Special Province, Indonesia - Chhuon Kong; Heru Hendrayana; Agung Setianto (Geological Engineering Department Universitas Gadjah Mada, 2015)
irrigation purposes within Bantul area which is located on Yogyakarta Volcanic Groundwater Basin, 47 existing data points were used complementary with the results of 30 groundwater samples analysis which were collected from dug and tub wells in various locations of study area. ECw, TDS, pH and major cations: Na+, Ca2+, Mg2+, K+,and anions: Cl????, HCO???? 3 , SO2???? 4 , NO???? 3 were analyzed as evaluation index. The relative tendency of ion in epm shows Ca2+>K+>Na+>Mg2+ and HCO???? 3 >Cl????>SO2???? 4 . Variations in groundwater composition by using Mg/Ca vs. Na/Ca molar ratio indicates that the groundwater is close to silicate rock with influence of clastic carbonate rock. Higher salinity approach to the west of the Bantul indicates that groundwater quality is controlled by clastic carbonate rock and expose limestone of Sentolo hills. Groundwater samples fall under class I suggested that groundwater is good and suitable for irrigation based on Doneen’s classification of permeability index and 78.37% is in excellent category by Wilcox classification on N%. According to the SAR values plotted in the USSL diagram, the majority of the groundwater samples belong to C2-S1 and C2-S2 class, indicating medium salinity and low sodium water which can be used for irrigation with little danger. The suitability of groundwater quality for agriculture is determined by thematic maps produced from ArcGIS Spatial Analyst based on FAO guideline. Salinity is the significant problem that has slight to moderate restriction effect on crops productivities in this area. The ECw map indicates that good groundwater quality for crops is at the middle to the east of study area close to Opak River, while at the western irrigation water is affected but yielding no reduction on rice productivity. However, it has slight to moderate restriction on sensitive crops indicated in thematic map of crops land with different yield potential. The agricultural land in which has yield potential of 100%, 90% and 75% is about 2727.90 ha (38.56%), 735.49 ha (10.39%) and 208.98 ha (2.95%) of the study area respectively. Key words: Irrigation groundwater quality, total dissolved solids (TDS), electrical conductivity (EC), evaluation index, ArcGIS Spatial Analyst, FAO guideline, yield potential.